Knowledge, Attitude and Practices Towards Dental Hazardous Waste Management Among Dentists in Tripoli Libya - Fatimah Buhour; Asam Aljwiw (AlQalam Journal of Medical and Applied Sciences, 2025)
Dental clinics and laboratories produce waste that differs in types and amount, which needs good management by using a disposal system. Biomedical Waste is any waste from humans during treatment, diagnosis, and research called Biomedical Waste which is include including dental clinic amalgam, impressions, dental materials, or sharp waste like needles, also another waste has high risk, such as blood, human tissues, and saliva, because they may lead to infection. This study was conducted to evaluate the level of behaviors and knowledge of hazardous waste management among dentists in Tripoli, Libya. This cross-sectional and descriptive study was conducted in a dental clinic in Tripoli, Libya, to evaluate the level of behaviors and knowledge of management of hazardous waste. It was found that the majority of the respondents were work as dentist more than 4 years (45.4%) then (25%) were work as dentist between 3-4 years then (18.4%) were work as dentist between 1-2 years then (9.7%), knowledge of infectious and non-infectious waste management showed 53.6% thought the infectious waste called waste originating from service units in hospitals, attitudes towards the management of infectious and non- infectious waste 95.4% of Sample members agree are infectious waste can cause diseases while 9 or 4.6% disagree, Behavior towards the management of infectious and non- infectious waste. 81.1% of them separate trash cans for infectious and non-infectious waste. Medical waste and dental waste need more and more research in the future, especially hazardous waste.